A conceptual index for benchmarking intermittent water supply in a water distribution system zone - Basson, Suzanne Esther; Jacobs, Heinz Erasmus; Loubser, Carlo (Water S. A., 2020)
Various challenges, such as limited freshwater resources, climate change impacts, rapid population growth, urbanisation and underinvestment in water supply infrastructure, have led to intermittent water supply (IWS) in potable water distribution systems. Earlier research has confirmed that IWS negatively impacts the consumers, the infrastructure and the water supply authorities. Water supply authorities need tools to help understand IWS and the associated implications. A new indexing framework involving the causes and impacts associated with IWS is presented in this paper. In addition, a novel approach allows for quantification of the severity of IWS based on knowledge of a few readily available inputs. The severity quantification is based on two ratios: the intermittency ratio is a temporal measurement, accounting for supply duration; the connection ratio describes spatial aspects, using the number of service connections affected. The indexing framework and quantification tool could lead to improved understanding of IWS and could assist water supply authorities faced with IWS to make informed decisions. Improved planning of remedial actions to mitigate or avoid risks associated with IWS is aided. The tools presented in this paper could be used as basis for future development of a key performance indicator.